Market definition of platform markets - Ralf Dewenter; Ulrich Heimeshoff; Franziska Löw (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2017)
Platform markets are characterized by the existence of indirect network effects that connect two or more market sides through a platform that internalizes these feedback effects. Conventional instruments of market definitions which consider price levels cannot easily applied in case of two-sided platform competition, as price structure of those markets are non-neutral. Instead of using prices, we use time series of quantities and simple correlation analysis to evaluate the substitutional relationship within two-sided media markets. As a benchmark model, we simulate a Cournot duopoly on order to calculate correlation coefficients for varying degrees of product differentiation and indirect network effects.
Keywords: D43; L40; L82; 330; two-sided markets; market definition; printed media; network effects